EFFICACY OF LUGOL’s IODINE AND GENTAMICIN IN REPEAT BREEDING COWS SUFFERING FROM UTERINE INFECTIONS - Singh, Narinder; Singh, Prahlad; Singh, Khushpreet; Kumar, Ajeet (The Indian Journal of Animal Reproduction, 2023)
The study was conducted to evaluate the efficacy of Lugol’s iodine (Intrauterine) and gentamicin (parenteral and post-AI) in repeat breeding cows (n=54). Repeat breeding cows were divided into two groups based upon the type of cervico-vaginal mucus (CVM) discharge, Group-1, n=28, repeat breeding cows having pus flakes or pus in uterine discharge; Group-2, n=26, repeat breeding cows having apparently clear CVM. For treatment purpose, 14 cows from Group-1 as Group 1(a) were infused 50 ml of 0.5% lugol solution once on day of estrus and 14 cows as Group 1(b) were injected gentamicin @ 5 mg per kg body weight intra muscular twice daily for three days, starting on the day of estrus. In the Group 2(a), repeat breeding cows (n=15) were infused gentamicin @ 2 mg body weight twenty hours post AI. Group 2(b) comprising of 11 cows served as untreated control. Overall conception rate in Group 1(a) was 72.7% as compared with 60% in Group 1(b) with 1.8 and 2.1 services per conception. Conception rate in repeat breeding cows having apparently normal CVM treated with post AI gentamicin intrauterine infusion didn’t improve as compared to control (40 vs. 36). It was concluded that the intra uterine infusion of lugol’s solution once on day of estrus in repeat breeding cows having purulent vaginal discharge was better in cleaning uterus of uterine infections than parenteral administration of gentamicin for three days